Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial (IPS) tentang Gejala Alam dan Cara Menghadapi Bencana Alam pada Peserta Didik Kelas VIB SD Negeri Kasreman melalui Metode Mind Map di Semester II Tahun Pelajaran 2018/2019 - Mudji Rahardjo (Universitas Sebelas Maret, 2019)
This research is a Class Action Research (CAR) with the purpose to analyze the learning outcome improvement of Social Science about Natural Phenomena and Facing Natural Disaster of the students of Class VI B the Elementary School of Kasreman withMind Map Method on the Second Semester of the 2018/2019 year academic. The subjects of this research are the students of Class VI B the Elementary School of Kasreman on the Second Semester of the 2018/2019 year academic as much as twenty children; consist of ten boys and ten girls. The data resources of this research are relating with learning activities and learning outcomes. Techniques of collecting data of this research are non test technique and test technique. The instruments of collecting data of this research are the sheets of observation, the camera application on the hand phone, the group tasks and also daily test. Technique of analyzing data of this research is comparative description. The procedure of this research is the Kemmis and Mc Taggart’s model. This research is consisting of two cycle; First Cycle and Second Cycle. Each cycle consists of two meetings. 1) Learning Social Science about Natural Phenomena and Facing Natural Disaster with Mind Map Method is going on a small group with different task, 2) Learning Social Science about Natural Phenomena and Facing Natural Disaster with Mind Map Method is a conceptual learning with text or picture, 3) Learning Social Science about Natural Phenomena and Facing Natural Disaster with Mind Map Method is improving the students’ learning activities on an actively discussing, actively answering the questions form the teacher and other students and actively asking the questions to the teacher,4) Learning Social Science about Natural Phenomena and Facing Natural Disaster with Mind Map Method is improving learning outcome on good category. The learning outcomes on the Early Condition are 63 for the average and 40% for the completeness. The learning outcomes on the First Cycle are 69,5 for the average and 55% for the completeness. The learning outcomes on the Second Cycle are 80,5 for the average and 85% for the completeness.